Modelling post-fire erosion on natural slope containing nesosilicate minerals - Luqma Illieana, Mat Isa (2017)
Post-fire increased hillslopes erosion and surface runoff. The effect increased by several magnitude when subjected to high intensity of precipitation during prolonged rainy season. With large rainfall events that exceed the storage capacity, erosion rates usually increase markedly due to destruction of the vegetation layer, the availability of highly erodible material and any changes in soil physical and hydrological properties, leading to an increase in runoff and a decrease in the strength of the soil surface that increases the detachability and transportation of sediment. In this study, various soil properties including specific gravity, atterberg limit, swell index and organic matter content were studied. The soil-water retention curve (SWCC) of all samples were also determined. For the purpose of this study, the moisture content were obtained for unburned and burned soil through chilled-mirror dew point technique test. The slope stability analysis were conducted by using GeoStudio software by SLOPE/W based on SWCC resulted. Parameters of shear strength were obtained and used for stability analysis with SLOPE/W software. Experimental result demonstrated that temperature 440°C, the liquid limit, organic matter content and SWCC were reduced and the swell index was eliminated. Heating the soil at 800°C and 1350°C completely eliminated the liquid limit, plastic limit, swell potential and organic content of soil tested. Based on the findings study, the lowest FOS or critical failure was natural burned sample. Followed by sample of burned 1350°C which also had a low value of FOS compared to natural unburned, burned 440°C and burned 800°C. From overall study, this modelling study examined that soil containing kyanite and quartz minerals are at a stable slope level whereas andalusite and mullite mineral soil types was shown a stability of less stable. Results proved the necessity of taking moisture content into account to express the post-fire erosion when processing stability analyses in order to achieve reliable and safe slope.